RATIONALE FOR THE STRATEGIC DEVELOPMENT VECTORS AND LANDMARKS OF REGIONAL SOCIO-ECONOMIC SYSTEMS AND TERRITORIES - SKOROBOGATA, LARYSA; OKSENIUK, TETIANA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Reforming the administrative-territorial structure of Ukraine, designed to decentralize the powers and capabilities of local authorities, primarily by expanding the list of their financial capabilities, and helped increase the level of responsibility of local authorities for the level of development of their territories. In this context, the processes of strategic management and substantiation of methodological approaches to the choice of vectors of strategic development, based on specific indicators of regional development, available opportunities and resources, began to gain special importance.The Ukraine’s administrative-territorial structure reform, aimed to decentralize the powers and capabilities of local authorities, first of all, by expanding the list of their financial capabilities, contributed to increasing the level of local leadership responsibility for their subordinate territories level of development. In this context, the processes of strategic management and substantiation of methodological approaches to the strategic development vectors choice, based on specific indicators of regional development, available opportunities and resources, began to gain special importance.The purpose of the study is to carry out a comparative analysis of the regional socio-economic systems development in Ukraine and propose an approach to the strategic development vectors choice and determination of its landmarks in each region.In the article substantiated the necessity of forming a unified approach to identification the strategic vectors and landmarks of regional development. Carried out the analysis of the gross regional product per capita dynamics in Ukraine on the basis of the interval distribution series construction. Five groups of regions are characterized by the level of studied indicator development and substantiated possible vectors and landmarks of strategic decisions.
Keywords: strategic development; reserves; regional socio-economic systems; development vectors